2005
DOI: 10.1108/jpbafm-17-01-2005-b004
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the limits of recreation: social costs of gambling in Southern Nevada

Abstract: This study seeks to find the dollar value of social costs of gambling. The authors use data from a survey of 99 members of Gamblers Anonymous (GA) groups in southern Nevada. The GA members were asked many questions about their behavior while they were active gamblers, such as how often they missed work because of gambling, how much they borrowed because of gambling, how much they stole because of gambling and their experiences with the judicial system and welfare systems because of gambling. Societal costs of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 4 publications
1
16
0
1
Order By: Relevance
“…This research asserted that the social cost of gambling in Macau had risen appropriately 163% (i.e., from $40 million to $106 million U.S. dollars) from 2003 to 2007. Similarly, Thompson and Schwer (2005) examined the dollar value of the social costs of gambling in Southern Nevada and discovered that each compulsive gambler imposed $19,711 (U.S. dollars) in social costs on other community members.…”
Section: Social Impactsmentioning
confidence: 98%
“…This research asserted that the social cost of gambling in Macau had risen appropriately 163% (i.e., from $40 million to $106 million U.S. dollars) from 2003 to 2007. Similarly, Thompson and Schwer (2005) examined the dollar value of the social costs of gambling in Southern Nevada and discovered that each compulsive gambler imposed $19,711 (U.S. dollars) in social costs on other community members.…”
Section: Social Impactsmentioning
confidence: 98%
“…Casino gaming has also been associated with domestic violence, divorce, bankruptcy, drug and alcohol abuse, risky or illicit sexual behavior, especially prostitution, and problem gambling (Allock, 2000;Chhabra, 2007;Petry, 2003). Thompson and Schwer (2005) examined the dollar value to social costs of gambling in Southern Nevada, discovering that each of the compulsive gamblers imposed social costs of US$19,711 on others in the community.…”
Section: Social Impactsmentioning
confidence: 99%
“…A National Gambling Impact Study Commission found that nearly 3 percent of the American population suffered from problem or pathological gambling afflictions (NGISC 1999). Other studies discuss the social costs in specific dollar terms (Thompson, Gazel, and Rickman 1996;Thompson and Schwer 2005). Dollar losses equate with ruined lives.…”
Section: Public Integrity Fall 2007 • 387mentioning
confidence: 97%